Literature review using the concept of Value Stream Mapping in the manufacturing industry - Antonio, Tito; Anggara, Sunu Surya; Sedubun, Elkiopas; Nurhaliza, Siti Farah; Setiawan, Rohmat; Setiawan, Indra; Azzahra, Shafa (Journal Industrial Servicess, 2023)
Value Stream Mapping (VSM) has become a valuable tool for decision-making and identifying opportunities for lean manufacturing practices. This study reviewed literature from various sources, including Google Scholar and Science Direct, to explore the application of VSM in different sectors of the manufacturing industry. The study used specific keywords, such as "Value Stream Mapping," "Manufacturing Industry," "Waste," and "Waiting Time" to identify relevant literature. The study analyzed 42 research papers published between 2017 and 2022 to examine the development and application of VSM in the manufacturing industry. VSM has been widely adopted in various industries such as automotive, food, and textile, among others, and has been used to create action plans that combine different lean techniques to achieve optimal results. The process of VSM involves two stages, which are describing the current and future conditions. From the descriptions, areas for improvement can be identified and developed to create a lean process. Based on the reviewed literature, VSM has been found to be highly effective in the manufacturing industry.